Anthropometrics of Polish children with osteogenesis imperfecta: a single-centre retrospective cohort study - E. Jakubowska-Pietkiewicz; A. Maćkowska; J. Nowicki; E. Woźniak; Nowicki Jakub (BMC Pediatrics, 2022)
Abstract Background Osteogenesis imperfecta (OI) causes a number of abnormalities in somatic development. The predominant symptoms are reduced bone mass and an increased risk of fractures as well as bone deformities and short stature. Due to the lack of causal treatment options, bisphosphonates are considered the gold standard of therapy. The aim of our study is to present selected anthropometric parameters (body weight, height, BMI) in children with type I and III of OI. Methods We performed a retrospective analysis of medical records of patients with osteogenesis imperfecta type I and III confirmed by genetic testing. The study group included individuals admitted to the Department in 2020. We analysed the anthropometric parameters of 108 children (receiving and not receiving bisphosphonates treatment). Results In the group of children with OI type I admitted for follow-up (group 1), the median weight percentile was 37, while in the group 2 it was 17. In the patients with OI type III (group 3), the median weight percentile was 0.1. The median height percentile in group 1 was 21, in group 2 it was 5, whereas in group 3 = 0.1. The differences in anthropometric measurements of the patients with OI type I and OI type III were statistically significant (p < 0.001). Among the analysed patients, an abnormal BMI was found in 41.67% of whom 37.78% were underweight, 48.89% were overweight and 13.33% were obese. Conclusion Considering prevalence of the disease, it is not only low stature but also abnormal BMI, and especially excessive body weight, that play an important role in the somatic development disorder.